Unmet need in rheumatology: reports from the Targeted Therapies meeting 2019 - Winthrop, Kevin L (Ann Rheum Dis, 2020)
OBJECTIVES: To detail the greatest areas of unmet scientific and clinical needs in rheumatology. METHODS: The 21st annual international Advances in Targeted Therapies meeting brought together more than 100 leading basic scientists and clinical researchers in rheumatology, immunology, epidemiology, molecular biology and other specialties. During the meeting, breakout sessions were convened, consisting of 5 disease-specific groups with 20–30 experts assigned to each group based on expertise. Specific groups included: rheumatoid arthritis, psoriatic arthritis, axial spondyloarthritis, systemic lupus erythematosus and other systemic autoimmune rheumatic diseases. In each group, experts were asked to identify unmet clinical and translational research needs in general and then to prioritise and detail the most important specific needs within each disease area. RESULTS: Overarching themes across all disease states included the need to innovate clinical trial design with emphasis on studying patients with refractory disease, the development of trials that take into account disease endotypes and patients with overlapping inflammatory diseases, the need to better understand the prevalence and incidence of inflammatory diseases in developing regions of the world and ultimately to develop therapies that can cure inflammatory autoimmune diseases. CONCLUSIONS: Unmet needs for new therapies and trial designs, particularly for those with treatment refractory disease, remain a top priority in rheumatology.